Public opinion on Indonesia's capital relocation policy: a netnographic analysis - Priyowidodo, Gatut; Angela Wijayanti, Chory (Faculty of Communications Science, Dr. Soetomo University, 2024)
The pros and cons of relocating the National Capital City have remained an unresolved issue across different regimes. When President Joko Widodo took concrete action to relocate IKN legally, the DPR approved through Law (UU) Number 3 of 2022 concerning the National Capital City (IKN), which was passed on January 18, 2022; the public immediately responded with acceptance and rejection. The dynamics of public conversations and comments through social media are intense. This research aims to answer public responses regarding the new relationship between the centre and the areas after passing the IKN Law. Using the netnography method, data were downloaded from the comment section of eight (8) YouTube accounts– CNBC Channel, detik.com, Narasi, TV One, Metro, RH Channel, RG Channel, and ILC Channel. This study employed thematic analysis and data processing with NVIVO 14 application. The research findings show that the eight YouTube accounts with more than 25,000 comments were categorised into two major themes. The first is an optimistic theme that expresses approval for the relocation of IKN. The reason is to improve welfare (Java-outside Java), long-term development planning, pro to the people, and show strong leadership to bridge the centre and regions. The two pessimistic themes expressed rejection, citing concerns about natural damage, potential corruption due to limited government finances, social inequality, and not being pro-people. This research recommends that the IKN relocation policy be understood optimistically and holistically, especially in central-regional relations and equitable distribution of economic access for a more prosperous Indonesia.